The Czech manuscripts : forgery, translation, and national myth - Cooper, David L., 1970- (NIU series in Slavic, East European, and Eurasian studies., 2023)
"A study of the nineteenth-century Czech forged manuscripts (Rukopis královédvorský and Rukopis zelenohorský) that examines the contexts of their creation and reception and their poetics"--